Extended Poisson's Ratio Range in Chiral Isotropic Elastic Materials. Issue 12 (4th September 2022) - Lakes, Roderic S.; Huey, Ballard; Goyal, Karan
Abstract : Poisson's ratio in chiral Cosserat elastic solids is considered. Chirality allows the Poisson's ratio to exceed classical bounds, even if the material is directionally isotropic and all elastic moduli are within thermodynamic limits based on strain energy density. Poisson's ratio in chiral rods depends on the chiral elastic constants as well as on the shear and bulk moduli, assumed positive. Poisson's ratio can be greater than 0.5 or smaller than −1 for slender chiral specimens. Abstract : Chirality allows the Poisson's ratio of directionally isotropic solids to exceed classical bounds: it can be greater than 0.5 or smaller than −1 for sufficiently slender chiral specimens. The objective of this study is to explore the influence of the chiral Cosserat elastic constants on the size effects in Poisson's ratio.